Association Between Drug Treatments and the Incidence of Liver Injury in Hospitalized Patients With COVID-19 - Gao, Suyu; Yang, Qingqing; Wang, Xuanxuan; Hu, Wen; Lu, Yun; Yang, Kun; Jiang, Qiaoli; Li, Wenjing; Song, Haibo; Sun, Feng; Cheng, Hong (Frontiers in Pharmacology, 2022)
The outbreak of coronavirus disease 2019 (COVID-19) has led to the emergence of global health care. In this study, we aimed to explore the association between drug treatments and the incidence of drug-induced liver injury (DILI) in hospitalized patients with COVID-19. A retrospective study was conducted on 5113 COVID-19 patients in Hubei province, among which 395 incurred liver injury. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated by Cox proportional hazards models. The results showed that COVID-19 patients who received antibiotics (HR 1.97, 95% CI: 1.55-2.51, p<0.001), antifungal agents (HR 3.10, 95% CI: 1.93-4.99, p<0.001) and corticosteroids (HR 2.31, 95% CI: 1.80-2.96, p<0.001) had a higher risk of DILI compared to non-users. Special attention was given to the use of parenteral nutrition (HR 1.82, 95% CI: 1.31-2.52, p<0.001) and enteral nutrition (HR 2.71, 95% CI: 1.98-3.71, p<0.001), which were the risk factors for liver injury. In conclusion, this study suggests that the development of DILI in hospitalized patients with COVID-19 needs to be closely monitored, and the above-mentioned drug treatments may contribute to the risk of DILI.